Pertentangan Pengaturan Pemilihan Anggota Komisi Independen Pemilihan di Aceh - Fuadi, Fuadi (Jurnal Konstitusi, 2016)
For the implementation of democratic elections required the existence of an institution independent of the general elections. The regulation of the formation of management bodies General Election in Aceh that was different from other regions are specifically regulated in Law Number 11 Year 2006 about Aceh Government and Qanun Aceh No. 7 of 2007 on General Election Organizer in Aceh. The purpose of this paper is to identify and explain the setting election of members of the general elections in Aceh and institute legal position of the general elections in Aceh. Based on the results of the study reveal any rules that conflict with the principles and legislation governing the establishment of the general elections in areas outside Aceh that assessed the existence of the institution of the general elections in Aceh are not independent because of the intervention of members of political parties.